2019
DOI: 10.3390/jcm8060864
|View full text |Cite
|
Sign up to set email alerts
|

The New Era for Reno-Cardiovascular Treatment in Type 2 Diabetes

Abstract: Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease in the developed world. Until 2016, the only treatment that was clearly demonstrated to delay the DKD was the renin-angiotensin system blockade, either by angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. However, this strategy only partially covered the DKD progression. Thus, new strategies for reno-cardiovascular protection in type 2 diabetic patients are urgently needed. In the last few years, hypoglycaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 76 publications
(112 reference statements)
0
22
0
Order By: Relevance
“…However, the dissociation of the curves for the outcomes that displayed the larger differences between groups in these trials (HHF and cardiovascular death) were observed during the first weeks suggesting that hemodynamic mechanisms, including mild natriuresis and reductions in blood pressure, may play a more prominent role [ 81 ]. Similarly, anti-inflammatory and antifibrotic effects and reversal of renal hypoxia of these agents could help towards a renoprotective action [ 94 , 95 , 96 ], but modulation of renal microcirculation is the most possible renoprotective mechanism [ 81 ]. Briefly, DM promotes renal injury through afferent arteriole vasodilation resulting in increased intraglomerular pressure and albuminuria.…”
Section: Current Therapeutic Approaches To Covid-19mentioning
confidence: 99%
“…However, the dissociation of the curves for the outcomes that displayed the larger differences between groups in these trials (HHF and cardiovascular death) were observed during the first weeks suggesting that hemodynamic mechanisms, including mild natriuresis and reductions in blood pressure, may play a more prominent role [ 81 ]. Similarly, anti-inflammatory and antifibrotic effects and reversal of renal hypoxia of these agents could help towards a renoprotective action [ 94 , 95 , 96 ], but modulation of renal microcirculation is the most possible renoprotective mechanism [ 81 ]. Briefly, DM promotes renal injury through afferent arteriole vasodilation resulting in increased intraglomerular pressure and albuminuria.…”
Section: Current Therapeutic Approaches To Covid-19mentioning
confidence: 99%
“…On the basis of the well-known plethora of biological substrates of the enzyme DDP-4, its crucial enzymatic inhibition could lead to several bio-molecular effects, ranging from metabolic (improving glycaemic control, total cholesterol and triglyceride levels, and weight neutrality) to cardiovascular (reducing risk factors, ameliorating cardiac function and vascular repair) general improvements [1,9,10,62].…”
Section: Dipeptidyl Peptidase-4 Inhibitors (Dpp4-is)mentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the predominant cause of death in diabetic patients [1,2]. Hyperglycaemic status activates multiple maladaptive signalling pathways involving endothelial dysfunction, which leads to the emergence and rapid progression of the atherosclerotic disease with distinct characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease (ESRD); in the past, the only treatment that was able to attenuate DKD was a renin-angiotensin system blockade (ACEi or ARB) but for the partial effectiveness of these agents is needed to delay or prevent progression to ESRD. Recently reno-cardiovascular safety profile of SGLT2 inhibitors and GLP-1RAs in diabetic patients has been suggested as a second line treatment in type 2 diabetic patients when it is not contraindicated [1]. Although they have shown a reassuring safety profile, unfortunately, the current guidelines do not fully allow us to identify the most appropriate drug according to a specific patient phenotype and attendant co-morbidities.…”
Section: Introductionmentioning
confidence: 99%